Evaluation of High-Performance Interference Canceller to Boost the Error Performance of The Wi-Fi 5 IEEE 802.11ac - Syafei, Wahyul Amien; Hidayatno, Achmad; Nurhayati, Oky Dwi; Nugraheni, Dinar (Diponegoro University, 2024)
The Wi-fi 5 IEEE 802.11ac can achieve throughput up to 6,933 Mbps by occupying 160MHz of bandwidth in each eight spatial streams with 256-QAM. It provides not only very high throughput but also high performance of wireless communications. However, due to the use of multiple antennas at both transmitter and receiver side which operate in the same frequency band; it experiences many interference signals. Therefore, a high-performance interference canceller is highly required to cancel these interferences and get the desired information back. The conventional interference cancellers are based on linear method, i.e. zero forcing and minimum mean square error. Both are simple but low in performance. This paper presents evaluation of a high-performance interference canceller based on maximum likelihood detection to boost the error performance of the wi-fi 5. Run test under in-door channel model demonstrates the superiority of this interference canceller. For target bit error rate of 10-4, it dramatically boosts the error performance by 16 dB and 17,5 dB compared to linear methods by the cost of very high complexity.